Physicians’ experiences with euthanasia: a cross-sectional survey amongst a random sample of Dutch physicians to explore their concerns, feelings and pressure - Kirsten Evenblij; H. Roeline W. Pasman; Johannes J. M. van Delden; Agnes van der Heide; Suzanne van de Vathorst; Dick L. Willems; Bregje D. Onwuteaka-Philipsen (BMC Family Practice, 2019)
Abstract Background Physicians who receive a request for euthanasia or assisted suicide may experience a conflict of duties: the duty to preserve life on the one hand and the duty to relieve suffering on the other hand. Little is known about experiences of physicians with receiving and granting a request for euthanasia or assisted suicide. This study, therefore, aimed to explore the concerns, feelings and pressure experienced by physicians who receive requests for euthanasia or assisted suicide. Methods In 2016, a cross-sectional study was conducted. Questionnaires were sent to a random sample of 3000 Dutch physicians. Physicians who had been working in adult patient care in the Netherlands for the last year were included in the sample (n = 2657). Half of the physicians were asked about the most recent case in which they refused a request for euthanasia or assisted suicide, and half about the most recent case in which they granted a request for euthanasia or assisted suicide. Results Of the 2657 eligible physicians, 1374 (52%) responded. The most reported reason not to participate was lack of time. Of the respondents, 248 answered questions about a refused euthanasia or assisted suicide request and 245 about a granted EAS request. Concerns about specific aspects of the euthanasia and assisted suicide process, such as the emotional burden of preparing and performing euthanasia or assisted suicide were commonly reported by physicians who refused and who granted a request. Pressure to grant a request was mostly experienced by physicians who refused a request, especially if the patient was ≥80 years, had a life-expectancy of ≥6 months and did not have cancer. The large majority of physicians reported contradictory emotions after having performed euthanasia or assisted suicide. Conclusions Society should be aware of the impact of euthanasia and assisted suicide requests on physicians. The tension physicians experience may decrease their willingness to perform euthanasia and assisted suicide. On the other hand, physicians should not be forced to cross their own moral boundaries or be tempted to perform euthanasia and assisted suicide in cases that may not meet the due care criteria.